IMPLEMENTASI MODEL PBL DENGAN MEDIA GANTUNGAN BAJU UNTUK MENINGKATKAN KEMAMPUAN MENGIDENTIFIKASI MAJAS PADA SISWA KELAS 5 SD - Tyas Pitaloka; Hariyadi; Bernadus Wahyudi Joko Santoso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to enhance fifth-grade students’ ability to identify figures of speech through the implementation of the Problem-Based Learning (PBL) model supported by “clothes hanger” media. The media were designed to facilitate contextual learning through visual and kinesthetic engagement, helping students grasp abstract literary concepts more concretely and enjoyably. The research employed a quasi-experimental design with a one-group pretest–posttest approach involving 30 fifth-grade students from SD Negeri 3 Tegowanu Wetan. Data were collected using a figure-of-speech identification test and analyzed through descriptive statistics and paired t-tests. The findings revealed a significant improvement in students’ mean scores from 72.10 (pretest) to 79.80 (posttest), with a mean gain of 7.70 points (t(29) = 4.26, p = 0.0002) and a moderate-to-strong effect size (Cohen’s d = 0.78). These results indicate that implementing PBL with simple yet contextual learning media effectively enhances students’ mastery of figurative language while fostering critical thinking, creativity, and collaboration skills.